(untitled) (International Seminar on Syariah and Law (INSLA), 2020)
Major shifts in the science and technology landscape have made the collection and analysis of digital evidence an increasingly important tool inresolving crimes as well as preparing the case for the trial in the court. Digital documents are known as electronic documents and it can be used as a means of proof in court. Also, digital documents can be used as evidence in the category of documents based on the definition given in Section 3 of the Syariah Court Evidence (Federal Territories) Act 1997[Act 561]. However, the digital document as a means of proof is still neededto be discussed in detail regarding its admissibility in the Syariah court. This is because there is no specific provisionaccording to Syariah Court Evidence lawon the use of it.This study,therefore,focuses on the concept of digital documents as evidence according to Syariah Law. This studyaims to discuss fromthe Islamic legal perspective on digital documents as a means of proof from the holy Quran, hadith, legal maxims and acts. This study also will focus on the admissibility of the digital document as evidence in the Syariah courtin Malaysia. The methodology of this study is a qualitative approach by using document analysis of article papers, journals, statutesand also related document references. The results show that the need to accept the admissibility of digital document as evidence very high, especially for use in the Syariah court. Studies show that the use of the digital document as evidence serves to supportother evidence presented in court.